Crosslinking of renewable polyesters with epoxides to form bio-based epoxy thermosets. (3rd January 2022) - Hanson, Kalin G.; Lin, Ching-Hsuan; Abu-Omar, Mahdi M.
Abstract: A series of renewable polyesters were crosslinked with epoxides in the presence of a nucleophilic base. Our previous study synthesized aromatic polyesters from a hydrogenated bis-isoeugenol (HB) and diacyl chloride monomers such as succinyl chloride (SU), adipoyl chloride (A), and sebecoyl chloride (SE) giving polyesters PHBSU, PHBA, and PHBSE. A lignin-derived epoxy was synthesized and compared to common industrial epoxies. The result of the cross-linking of the polyesters with these epoxides improved the thermal properties, increasing Tg from 61 °C to 98 °C for PHBSU-based thermosets, 43 °C–105 °C for PHBA-based thermosets, and 19 °C–103 °C for PHBSE-based thermosets. The mechanical properties showed storage moduli of 4.7–19 MPa and tensile stress of up to 68 MPa. The utilization of a polyester as a crosslinker for epoxy thermosets is a largely untapped mechanism and can expand the library of thermoset materials, especially for bio-based renewable thermoset materials. Graphical abstract: Image 1 Highlights: Active ester and epoxy chemistry is a valid curing mechanism for thermosets. Renewable polyesters as an active ester source gives high % biocontent material. Bio-based epoxides can be utilized to further increase the % biocontent. Cured material showed improved thermal and mechanical properties.